The Effectiveness of Anger Management Training in Reducing Bullying Behavior among School-Age Children - Tryastuti, Dini (International Journal of Nursing and Health Services (IJNHS), 2022)
Introduction: Bullying is frequently violent behavior by an individual or group against a weak individual. Bullying behavior may have a negative effect on both a bully and a victim. The Incident of bullying has increased. Therefore it needs to get serious attention. Anger management training was one intervention for decreasing bullying behavior. The prior intervention rarely used anger management that included calming techniques, cognitive restructuring, and assertiveness (Communication Technique). Objective: This study aimed to examine the effect of anger management training in reducing bullying behavior in school-age children in Cimanggis Depok City. Method: The design of this study was a quasi-experiment pre-posttest with a control group. The study sample consisted of 80 elementary school students who have experienced bullying others, the intervention group had 40 respondents, and the control group had 40 respondents. The sample of the study was selected by random sampling technique. Result: The result showed that anger management training effectively reduced bullying behavior in school-age children (p 0,001). Recommendation: It was recommended to use anger management training in reducing bullying behavior among school-age children